The Presentation of Speaking Materials in English Textbook for High School Level - Annisrina Fajri Nugraheni; Sindi Dian Safiroh; Putri Rahayu; Putri Widiarsih; Rini Estiyowati Ikaningrum (Jurnal Langua, 2021)
The purpose of this study is to analyze the performance of speaking material in the textbook "English for Senior High School 12th Class Curriculum 2013 Revised 2018" based on the criteria of an excellent textbook proposed by Savignon (2008) to illustrate the relevance of speaking material in the book. This textbook was published by the Ministry of Education and Culture of the Republic of Indonesia for twelfth-grade students through the 2013 curriculum and described the order of speaking material in the textbook. The writers also found that the relevance of the material spoke sufficiently with the 2013 English Language Competency Standards. However, some competencies did not follow the competency. The reason was that the textbook did not present the material in speaking.